Pengaruh Motivasi Ekstrinsik, Self Efficacy, dan Work Life Balance terhadap Kinerja Karyawan Produksi Rokok 12 PT Praoe Lajar - Anissa Azhari; Adhi Pradiptya; Edy Suryawardana (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This research is motivated by the existence of factors that influence employee performance in a company. The aim of this study is to determine the influence of extrinsic motivation, self-efficacy, and work-life balance on the performance in the 12-cigarette production employees at PT Praoe Lajar Semarang. The population in this study was 120 employees in the 12-cigarette production department at PT Praoe Lajar Semarang. The sample used was purposive sampling, with 60 respondents. The instrument used was a questionnaire and the measurement used a likert scale. The test tool used was SPSS Version 26. Data analysis methods included validity testing, reliability testing, respondent description analysis, multiple linear regression, classical assumption testing, t-test, and coefficient of determination testing. The results indicate that extrinsic motivation has a positive and significant effect on employee performance, indicating that employees are motivated by external influences to improve their performance. Self-efficacy has a positive and significant effect on employee performance, indicating that employees are satisfied with their ability to improve their performance. Work life balance has a positive and significant effect on employee performance, meaning that the higher the work life balance of employees, the better their performance will be.